Difficulties of Educating People With Socio-Educational Needs - Simonenko, S.M. (2020)
The publication “Problems of introducing inclusive education in the social environment of Ussuriysk city” examines the complex problems and sociocultural processes of society concerning people with special socio-educational needs, people with disabilities and people with physical disabilities. The paper briefly explains the essence of inclusive education and the problems of its introduction into the social environment of small towns, for example, the city of Ussuriysk, when, along with the development of defectological schools and the government order for them, there is a lack of understanding of the need for such education, an indifferent, callous attitude towards disadvantaged physical disabilities to people.